Sensitivity of the cochlear nerve to acoustic and electrical stimulation months after a vestibular labyrinthectomy in guinea pigs - Brown, Daniel; Mukherjee, P.; Pastras, C.; Gibson, W.; Curthoys, I. (2016)
© 2016. Single-sided deafness patients are now being considered candidates to receive a cochlear implant. With this, many people who have undergone a unilateral vestibular labyrinthectomy for the treatment of chronic vertigo are now being considered for cochlear implantation. There is still some concern regarding the potential efficacy of cochlear implants in these patients, where factors such as cochlear fibrosis or nerve degeneration following unilateral vestibular labyrinthectomy may preclude their use. Here, we have performed a unilateral vestibular labyrinthectomy in normally hearing guinea pigs, and allowed them to recover for either 6 weeks, or 10 months, before assessing morphological and functional changes related to cochlear implantation. Light sheet fluorescence microscopy was used to assess gross morphology throughout the entire ear. Whole nerve responses to acoustic, vibrational, or electrical stimuli were used as functional measures. Mild cellular infiltration was observed at 6 weeks, and to a lesser extent at 10 months after labyrinthectomy. Following labyrinthectomy, cochlear sensitivity to high-frequency acoustic tone-bursts was reduced by 16 ± 4 dB, vestibular sensitivity was almost entirely abolished, and electrical sensitivity was only mildly reduced. These results support recent clinical findings that patients who have received a vestibular labyrinthectomy may still benefit from a cochlear implant.